Establishment of a Mycoplasma hyorhinis challenge model in 5-week-old piglets - Földi, Dorottya; Nagy, Zsófia Eszter; Belecz, Nikolett; Szeredi, Levente; Földi, József; Kollár, Anna; Tenk, Miklós; Kreizinger, Zsuzsa; Gyuranecz, Miklós (Frontiers in Microbiology, 2023)
Mycoplasma hyorhinis is an emerging swine pathogen with high prevalence worldwide. The main lesions caused are arthritis and polyserositis and the clinical manifestation of the disease may result in significant economic losses due to the decreased weight gain and enhanced medical costs. Our aim was to compare two challenge routes to induce M. hyorhinis infection using the same clinical isolate. Five-week-old, Choice hybrid pigs were inoculated on two consecutive days by intravenous route (Group IV-IV) or by intravenous and intraperitoneal route (Group IV-IP). Mock-infected animals were used as control (Control Group). After challenge, the clinical signs were recorded for 28 days, after which the animals were euthanized. Gross pathological and histopathological examinations, PCR detection, isolation and genotyping of the re-isolated Mycoplasma sp. and culture of bacteria other than Mycoplasma sp. were carried out. ELISA test was used to detect anti-M. hyorhinis immunoglobulins in the sera of all animals. Pericarditis and polyarthritis were observed in both challenge groups, however the serositis was more severe in Group IV-IV. Statistically significant differences were detected between the challenged groups and the Control Group regarding the average daily weight gain, pathological scores and ELISA titers. Additionally, histopathological scores in Group IV-IV differed significantly from the scores in the Control Group. All re-isolated strains were the same or a close genetic variant of the original challenge strain. Our results indicate that both challenge routes are suitable for modelling the disease. However, due to the evoked more severe pathological lesions and the application being similar to the hypothesised natural route of infection in Group IV-IV, the two-dose intravenous challenge is recommended by the authors to induce serositis and arthritis associated with M. hyorhinis infection.